2022
DOI: 10.1038/s41598-022-05299-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral coping phenotypes and associated psychosocial outcomes of pregnant and postpartum women during the COVID-19 pandemic

Abstract: The impact of COVID-19-related stress on perinatal women is of heightened public health concern given the established intergenerational impact of maternal stress-exposure on infants and fetuses. There is urgent need to characterize the coping styles associated with adverse psychosocial outcomes in perinatal women during the COVID-19 pandemic to help mitigate the potential for lasting sequelae on both mothers and infants. This study uses a data-driven approach to identify the patterns of behavioral coping strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…A similar result was obtained in a cross-sectional survey during the pandemic ( 16 ). In addition, it is confirmed that passive coping strategies of pregnant women are correlated with depression, anxiety, and psychological distress ( 63 ). Daglar et al also suggested that optimistic coping styles with stress were correlated with pregnant women's self-confidence ( 64 ).…”
Section: Discussionmentioning
confidence: 88%
“…A similar result was obtained in a cross-sectional survey during the pandemic ( 16 ). In addition, it is confirmed that passive coping strategies of pregnant women are correlated with depression, anxiety, and psychological distress ( 63 ). Daglar et al also suggested that optimistic coping styles with stress were correlated with pregnant women's self-confidence ( 64 ).…”
Section: Discussionmentioning
confidence: 88%
“…Also, women with depressive symptoms show more avoidant behaviors than those with no levels of depression (68). A change of the coping strategies through psychoeducational programs is one of the aims of the therapeutic approaches for reducing vulnerability to stress in patients at risk of depression after childbirth (69). In fact, psychological interventions based on cognitive behavioral techniques are encouraged for improving dysfunctional coping strategies (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, increased social media exposure during the COVID pandemic is associated with higher rates of depression and anxiety, perhaps due to the ease of access to distressing information. ( Werchan et al, 2022 , Gao et al, 2020 , Geirdal et al, 2021 ) Thus, women in this study found themselves in a bind between their desire to connect and the negative mental health effects of social media use. It is important to continue to further understand how to utilize the beneficial aspects of social media while minimizing the psychological harm.…”
Section: Discussionmentioning
confidence: 69%
“…( Morganstein and Ursano, 2020 ) Likewise, during this COVID-19 pandemic, women during the perinatal period reported high levels of stress, anxiety, and depression ( Basu et al, 2021 , Farewell et al, 2020 , Tomfohr-Madsen et al, 2021 ); those who engaged in passive coping (e.g., higher use of screen time, intake of comfort foods) experienced higher levels of psychological distress. ( Werchan et al, 2022 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation